Greenhouse Gas Emissions from Subtropical Agriculture Fields Decrease Over Time. (8th January 2021) - Adamczyk, Bartosz; Fall, Thioro; Heiden, Katie; Smyth, Ashley R.; Brym, Zachary
Abstract: Expansion of cultivated lands and field management impacts greenhouse gas (GHG) emissions from agriculture soils. Soils naturally cycle GHGs and can be sources or sinks depending on physical and chemical properties affected by cultivation and management status. We looked at how cultivation history influences GHG emissions from subtropical soils. We measured CO2, N2 O, and CH4 fluxes, and soil properties from newly converted and continuously cultivated lands during the summer rainy season in calcareous soils from south Florida. Newly converted soils had more soil organic matter (OM), more moisture, higher porosity, and lower bulk density, leading to more GHG emissions compared to historically cultivated soils. Although more nutrients make newly converted lands more desirable for cultivation, conversion of new areas for agriculture was shown to release more GHGs than cultivated lands. Our data suggest that GHG emissions from agricultural soils may decrease over time with continued cultivation.